Positive affect between close friends: Brain-behavior associations during adolescence. (3rd March 2020) - Woods, Brittany K.; Forbes, Erika E.; Sheeber, Lisa B.; Allen, Nicholas B.; Silk, Jennifer S.; Jones, Neil P.; Morgan, Judith K.
ABSTRACT: Identifying the neural correlates of positive interactions between friendship dyads may provide insights into mechanisms associated with adolescent social development. Forty-eight 14- to 18-year-old typically developing adolescents were video-recorded discussing a shared positive event with a close friend and subsequently viewed clips during an fMRI scan of that friend during the interaction and of an unfamiliar peer in a similar interaction. Adolescents also reported on their positive affect in daily life while with friends using ecological momentary assessment. We used multivariate repeated measures models to evaluate how positive affect with friends in the laboratory and in daily life was associated with neural response to friend and stranger positive and neutral clips. Adolescents who exhibited more positive affect when with friends in the laboratory showed less dorsolateral prefrontal cortex to friend positive clips. More positive affect when with friends in daily life was associated with less bilateral anterior insula response to friend positive clips, but greater left anterior insula response to stranger positive clips. Findings provide information on the role of lateral prefrontal cortex and anterior insula in enjoyment of friendships during adolescence.